Intestinal anti-inflammatory and visceral analgesic effects of a Serpylli herba extract in an experimental model of irritable bowel syndrome in rats - Ruiz-Malagón, Antonio Jesús; Rodríguez-Sanchez, María José; Rodríguez-Sojo, María Jesús; Vezza, Teresa; Pischel, Ivo; Algieri, Francesca; Rodríguez-Cabezas, María Elena; Rodríguez-Nogales, Alba; Gálvez, Julio (Frontiers in Pharmacology, 2022)
Ethnopharmacological relevance: Serpylli herba extract (SHE), composed of the aerial parts of wild thyme (Thymus serpyllum L.) (Lamiaceae family), is traditionally used in Europe and North Africa to treat diarrhea, gastric ulcers, intestinal parasites and upper respiratory tract infections. Recently, SHE has generated a great interest for irritable bowel syndrome (IBS) management, probably due to its intestinal anti-inflammatory properties shown in experimental colitis and the fact that its active components could preserve the intestinal barrier integrity, which is altered in patients with IBS. Aim of study: We aimed to test the effects of a SHE in a rat experimental model resembling human IBS. Materials and Methods: IBS was provoked by deoxycholic acid (DCA). Rats were then treated with SHE (100 mg/kg) or gabapentin (70 mg/kg) and different inflammatory and gut barrier integrity markers were evaluated. Moreover, several gut hypersensitivity and hyperalgesia determinations were performed. Results: SHE improved referred pain and visceral hypersensitivity. Additionally, SHE enhanced immune status by downregulating of the expression of the pro-inflammatory mediators Il-1β, Il-6, Ifn-γ, Tlr-4 and the inducible enzyme Cox-2, thus inducing visceral analgesia, and promoting the restore of the gut barrier function by upregulating the mucins Muc-2 and Muc-3. These anti-inflammatory effects could be related to its action on mast cells since it significantly inhibited the β-hexosaminidase production in RBL-2H3 cells. Lastly, SHE also seems to modulate the serotonin pathway by restoring the altered expression of the 5-HT receptors Htr-3 and Htr-4. Conclusions: SHE could be considered a potential new treatment for IBS, since it ameliorates hypersensitivity, visceral hyperalgesia and inflammation. These beneficial effects may be due to the inhibition of mast cells degranulation and serotonin pathway.